2012
DOI: 10.1016/j.breast.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with upstaging from ductal carcinoma in situ following core needle biopsy to invasive cancer in subsequent surgical excision

Abstract: Upstaging was associated with lesions that were large, palpable or high grade. It was also associated with use of the 14-gauge needle method. Our scoring system might be helpful to identify patients who do not require sentinel lymph node biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 19 publications
11
69
3
1
Order By: Relevance
“…HG-DCIS, in comparison to non-high-grade counterparts, has a significantly higher rate of recurrence. 23,24 Recurrence tends to occur earlier and more often as invasive carcinoma. 25,26 Likewise, high nuclear grade in DCIS on biopsy specimens is, among other factors, a significant risk factor for invasive carcinoma on excision.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…HG-DCIS, in comparison to non-high-grade counterparts, has a significantly higher rate of recurrence. 23,24 Recurrence tends to occur earlier and more often as invasive carcinoma. 25,26 Likewise, high nuclear grade in DCIS on biopsy specimens is, among other factors, a significant risk factor for invasive carcinoma on excision.…”
Section: Discussionmentioning
confidence: 98%
“…25,26 Likewise, high nuclear grade in DCIS on biopsy specimens is, among other factors, a significant risk factor for invasive carcinoma on excision. 24,27 The role of changes associated with tumor regression in predicting HG-DCIS recurrence has been explored, with mixed results. Some authors identified that periductal inflammation and fibrosis are significantly associated with tumor recurrence and invasive carcinoma on excision.…”
Section: Discussionmentioning
confidence: 99%
“…The two models were selected using data of the meta-analysis study [1] and the multivariate analysis study [2]. Selected meta-analysis study was the only study of that kind reported prior to the period of research, and we selected the largest Korean study among the many multivariate analysis studies.…”
Section: Case Descriptionmentioning
confidence: 99%
“…The multivariate analysis study [2] showed 216 cases of invasive cancer among 506 cases of DCIS. The model of the multivariate analysis study is given as…”
Section: Case Descriptionmentioning
confidence: 99%
See 1 more Smart Citation